(untitled) (Journal of Hama University, 2024)
This study aims to measure the impact of asymmetric monetary shocks on the rate of inflation in the Syrian economy. The financial data extracted from the reports published by the Central Bank of Syria and the publications of the Central Bureau of Statistics in the Syrian Arab Republic were relied upon, and then statistical analysis of these data was performed for the time series (2011-2022) using the statistical program (EVIEWS10). The results of the study showed the existence of a long-term equilibrium relationship with statistical significance between the positive and negative monetary shocks and the inflation rate, and the existence of asymmetry in the effect of the different monetary shocks in strength and time gap, and that the relationship between positive and negative monetary shocks and the inflation rate is non-linear, and it was found that there is a statistically significant causal relationship between the asymmetric monetary shocks and the inflation rate, as the positive and negative monetary shocks cause positive and negative changes in the inflation rate.